Central Bank Autonomy and Price Stability in Sub-Saharan Africa: Implications for the Bank of Central African States (BEAC) (Global Journal of Human-Social Science, 2025)
The purpose of this paper is to validate the link between the autonomy of the Central Bank and inflation An econometric modeling of the relationship between inflation the autonomy of the Central Bank and economic performance variables will allow to answer to the problem that the reduction of the inflationary bias passes by the autonomy of the Central Bank Indeed by adopting a legal and real measure of autonomy Cukierman et al 1992 for ten 10 Central Banks in Sub-Saharan Africa over the period 1980-2017 the static panel regression partially confirms the expected relationship Result which proves that the condition of the autonomy of the Central Bank can only be necessary and not sufficient to price stability
Keywords: central bank autonomy; price stability; static panel data; sub-saharan africa (SSA)